High-intensity laser-driven oxygen source from CW laser-heated titanium tape targets - Kondo,K; Nishiuchi,M; Sakaki,H; Dover,NP; Lowe,HF; Miyahara,T; Watanabe,Y; Ziegler,T; Zeil,K; Schramm,U; Ditter,EJ; Hicks,GS; et al. (Crystals, 2020)
The interaction of high-intensity laser pulses with solid targets can be used as a highly charged, energetic heavy ion source. Normally, intrinsic contaminants on the target surface suppress the performance of heavy ion acceleration from a high-intensity laser–target interaction, resulting in preferential proton acceleration. Here, we demonstrate that CW laser heating of 5 µm titanium tape targets can remove contaminant hydrocarbons in order to expose a thin oxide layer on the metal surface, ideal for the generation of energetic oxygen beams. This is demonstrated by irradiating the heated targets with a PW class high-power laser at an intensity of 5 × 1021 W/cm2, showing enhanced acceleration of oxygen ions with a non-thermal-like distribution. Our new scheme using a CW laser-heated Ti tape target is promising for use as a moderate repetition energetic oxygen ion source for future applications.